Sovereignty and responsibility power, norms and intervention in international relations - Moses, Jeremy (Palgrave Macmillan, 2014)
"For the past two decades, arguments in favour of the use of force for humanitarian purposes have rested heavily upon the concept of 'sovereignty as responsibility'. Yet the many complex challenges posed by crises in places such as Kosovo, Libya, Syria and Ukraine have illustrated the continuing failure of such normative arguments to transform the practice of international relations. This book responds to these theoretical and practical problems by drawing a sharp distinction between two strands of thought on the concept of sovereignty, one focused on power and the other on moral and legal responsibilities. Through analysis of case studies of Kosovo and Libya and consideration of the concept of the world state, the weaknesses and dangers of normative claims in support of humanitarian intervention are exposed and analysed"..